2020
DOI: 10.1242/dev.187666
|View full text |Cite
|
Sign up to set email alerts
|

Vein patterning by tissue-specific auxin transport

Abstract: Unlike in animals, in plants vein patterning does not rely on direct cell-cell interaction and cell migration; instead, it depends on the transport of the plant hormone auxin, which in turn depends on the activity of the PIN-FORMED1 (PIN1) auxin transporter. The current hypotheses of vein patterning by auxin transport propose that in the epidermis of the developing leaf PIN1-mediated auxin transport converges to peaks of auxin level. From those convergence points of epidermal PIN1 polarity, auxin would be tran… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…At all analyzed stages, E4259>>erGFP was expressed in trichomes but was not expressed in mature stomata (Figure 3B‐H). In conclusion, expression of E4259>>erGFP resembles that of ARABIDOPSIS THALIANA MERISTEM LAYER1 , 43,44 which marks epidermal cells and whose promoter is used to drive epidermis‐specific expression (eg, References 45‐48).…”
Section: Resultsmentioning
confidence: 93%
“…At all analyzed stages, E4259>>erGFP was expressed in trichomes but was not expressed in mature stomata (Figure 3B‐H). In conclusion, expression of E4259>>erGFP resembles that of ARABIDOPSIS THALIANA MERISTEM LAYER1 , 43,44 which marks epidermal cells and whose promoter is used to drive epidermis‐specific expression (eg, References 45‐48).…”
Section: Resultsmentioning
confidence: 93%
“…7c) (Scarpella et al ., 2006). Interestingly, recent work has shown that epidermal accumulation of PIN1 is dispensable; Arabidopsis seedlings that lack epidermal PIN1 develop venation patterns indistinguishable from the wild‐type (Govindaraju et al ., 2020). However, PIN1 presence in the inner tissues is essential for normal leaf vein development (Govindaraju et al ., 2020).…”
Section: Ontogeny Of Leaf Veinsmentioning
confidence: 99%
“…Interestingly, recent work has shown that epidermal accumulation of PIN1 is dispensable; Arabidopsis seedlings that lack epidermal PIN1 develop venation patterns indistinguishable from the wild‐type (Govindaraju et al ., 2020). However, PIN1 presence in the inner tissues is essential for normal leaf vein development (Govindaraju et al ., 2020). Third and higher rank veins display a different PIN1 profile in that no epidermal PIN1 expression is observed; instead expression appears in a single row of cells starting from an existing PED or mature vein with PIN1 oriented towards them (Fig.…”
Section: Ontogeny Of Leaf Veinsmentioning
confidence: 99%
“…LEC2 is a positive regulator of selenium-induced YUC-mediated auxin biosynthesis in Arabidopsis thaliana somatic embryogenesis [81,82]. The overexpression of miR167c inhibited the formation of selenium and increases the expression of LEC2 [12], and at the same time interfered with PIN-FORMED1 (PIN1) in cell membrane of embryogenic callus affected auxin transport [83][84][85]. miR167 targeted ARF6 and ARF8, effects on auxin synthesis and local auxin transport in embryogenic callus, thus regulating Arabidopsis thaliana somatic embryogenesis.…”
Section: Mir167 Regulates Plant Embryo and Seed Developmentmentioning
confidence: 99%